Promoting interdisciplinarity and the timely integration of palliative care through the development and implementation of a blended learning elective for medical students - Batzler, Yann-Nicolas; Schallenburger, Manuela; Sammer, Tabea; Haussmann, Jan; Tamaskovics, Bálint; Rehlinghaus, Marc; von Schreitter, Julia; Otten, Stefanie; Fohler, Corinna; Schwartz, Jacqueline; Karger, André; Niegisch, Günter; et al. (GMS Journal for Medical Education)
Background: Given demographic changes and a rising prevalence of oncological diseases, understanding the importance of interdisciplinary collaboration and a timely integration of palliative care is crucial. However, both are underrepresented in medical curricula. To address this gap, we introduced a new elective in which students follow the journey of a fictitious patient with prostate cancer from diagnosis until death. Method: The elective was conducted through repeated joint meetings by a multi-professional and interdisciplinary (palliative care, urology, radiation oncology, psychosomatic medicine) team. Alongside its development, an outcome evaluation was designed to assess satisfaction (Likert scale) and learning gains (comparative self-assessment, CSA [%]). After pilot testing, the content and structure were adapted. The elective followed a blended learning approach. The content covered guideline-adherent treatment of prostate cancer, breaking bad news, initial contact with palliative care, symptom control based on the total pain concept. Results: Students (n=8) expressed high satisfaction. They found the structure comprehensible and considered the content valuable for medical practice. Students gained knowledge, especially in defining total pain (83%) and the indication of the timely integration of specialized palliative care (77%). Conclusion: Using prostate cancer as an example disease, we integrated multiple disciplines into treatment strategies, demonstrating the benefits of multi-professional and multidisciplinary collaboration. This approach aids in identifying patients who could benefit from palliative care. Our concept is adaptable to other tumor types and settings, enhancing awareness of patient-centered issues that are often overlooked in medical curricula.